ETIKA PENYIARAN DALAM PERSPEKTIF ISLAM - Abdul Rachman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
From the point of view of broadcasters as media, Malvin L. DeFleur & Everet E. Dennis, Understanding Mass Communication, which is a type of media that uses electromagnetic instrument in conveying the message to the audience simultaneously. While broadcasting is called broadcasting has the meaning as: